S7commTrace: A High Interactive Honeypot for Industrial Control System Based on S7 Protocol - Xiao, Feng; Chen, Enhong; Xu, Qiang (Information and Communications Security, 2018)
Intensively happened cyber-attacks against industrial control system pose a serious threat to the critical national infrastructure. It is significant to capture the detection and the attacking data for industrial control system by means of honeypot technology, as it provides the ability of situation awareness to reveal potential attackers and their motivations before a fatal attack happens. We develop a high interactive honeypot for industrial control system-S7commTrace, based on Siemens’ S7 protocol. S7commTrace supports more function codes and sub-function codes in protocol simulation, and improves the depth of interaction with the attacker to induce more high-level attacks effectively. A series of comparative experiments is carried out between S7commTrace and Conpot, by deploying these two kinds of honeypots under the same circumstance in four countries. Data captured by these two kinds of honeypots is analyzed respectively in four dimensions, which are query results in Shodan, count of data and valid data, coverage of function code and diversity of source IP address. Experiment results show that S7commTrace has better performance over Conpot.